Dynamic regulation of HIF1Α stability by SUMO2/3 and SENP3 in the human placenta. (April 2016) - Bhattacharjee, Jayonta; Alahari, Sruthi; Sallais, Julien; Tagliaferro, Andrea; Post, Martin; Caniggia, Isabella
Abstract: Introduction: Hypoxia-induciblef actor 1A (HIF1A) stability is tightly regulated by hydroxylation and ubiquitination. Emerging evidence indicates that HIF1A is also controlled by the interplay between SUMO-specific ligases, which execute protein SUMOylation, and Sentrin/SUMO-specific proteases that de-SUMOylate target proteins. Given the significance of HIF1A in the human placenta, we investigated whether placental HIF1A is subject to SUMOylation in physiological and pathological conditions. Methods: Placentae were obtained from normal and pregnancies complicated by preeclampsia. Human choriocarcinoma JEG3 cells were maintained at either 21% or 3% oxygen or exposed to sodium nitroprusside (SNP). Cells were transfected with SUMO2/3 constructs with and without Mg132, a proteasome inhibitor. Expression, distribution and associations of SUMO/SENPs and HIF1A were evaluated by Western blotting, immunohistochemistry and co-immunoprecipitation. Results: HIF1A-SUMO2/3 associations peaked at 9–10 weeks, while its deSUMOylation by SENP3 was greatest at 10–12 weeks. In E-PE, HIF1A deSUMOylation by SENP3 was significantly elevated, while HIF1A-SUMO2/3 associations remained constant. In vitro, overexpression of SUMO2/3 de-stabilized HIF1A in hypoxia, and abrogated HIF1A expression following Mg132 treatment in normoxia. Hypoxia and SNP treatments promoted SENP3 nuclear redistribution from nucleoli to the nucleoplasm where it associates with HIF1A. Conclusion: During early placental development, SUMOylation events control HIF1A stability in an oxygen-dependent manner. In E-PE, enhanced deSUMOylation of HIF1A by SENP3 may in part contribute to increased HIF1A activity and stability found in this pathology. Highlights: SUMO2/3 and SENP3 regulate HIF1A stability during placental development. HIF1A SUMOylation by SUMO2/3 leads to HIF1A degradation. SENP3 activation involving its nuclear redistribution is induced in hypoxia. HIF1A de-SUMOylation by SENP3 is responsible for high HIF1A levels in preeclampsia.